Management of Policy Implementation and Perceived Organizational Performance: The Mediating Effect of Implementer Disposition - Beatrix Antoneta Manggo; Vince Tebay; Jacobus Rico Kuntag (Research Horizon, 2026)
This study investigates the direct and indirect effects of organizational resources, bureaucratic structure, and implementation communication on perceived public organizational performance through implementer disposition at the Nabire Regency AIDS Commission. A cross-sectional survey involved 80 respondents from government agencies, health facilities, civil society organizations, working groups, and target-group networks. Structural equation modeling with maximum likelihood estimation was used, while model fit and indirect effects were examined through Bollen–Stine and bias-corrected bootstrapping with 5,000 resamples. Model fit was mixed: CMIN/DF = 1.427 and RMSEA = 0.073 were acceptable, and Bollen–Stine p = 0.359 did not reject model fit, although several incremental and absolute fit indices remained below their reference values. Resources, bureaucratic structure, and communication were positively related to implementer disposition under maximum likelihood estimation, but the paths from structure and communication were not robust in the bootstrap test at the 5% level. Resources, communication, and disposition were positively related to perceived performance, whereas the direct path from bureaucratic structure was not significant. The model explained 56.0% of disposition variance and 84.9% of perceived-performance variance. Disposition significantly mediated the relationships of resources and communication with performance, but not the relationship of bureaucratic structure with performance.